PELATIHAN GAME EDUKATIF BERBASIS SCRATCH BAGI GURU SEKOLAH DASAR - Mamik Usniyah Sari; Muhammad Harist Murdani; Nurwahyudi Widhiyanta (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
This Community Engagement Program (PPM) was implemented at Al Kautsar Elementary School, Benowo, Surabaya, an institution with more than 300 students that demonstrates strong potential for digital literacy development but continues to face challenges in integrating technology-based learning media. The main issues identified include the low competence of teachers in utilizing coding tools such as Scratch, the absence of interactive digital media integration in the learning process, and the limited availability of appropriate teaching resources. In response to the Ministry of Education, Culture, Research, and Technology’s policy to integrate coding and artificial intelligence (AI) into the curriculum starting in 2025, the proposing team offers a solution through intensive training and teacher mentoring in designing and utilizing Scratch-based learning media, supported by student involvement under the MBKM (Freedom to Learn – Independent Campus) scheme. The program’s expected outputs include improved teacher competence in applying Scratch, the development of at least three interactive digital learning media, the preparation of a Scratch teaching module for elementary school teachers, documentation of student involvement, and dissemination of results through CSR-PKM proceedings and mass media. The implementation method consists of five stages: socialization, practice-based training, classroom application of the media, mentoring and evaluation, and program sustainability planning through the development of teachers as internal trainers. This program is expected to support the implementation of the new curriculum, enhance digital literacy, and foster a technology-based learning ecosystem in elementary education.